DYNAMIC DE-EXCITATION PERFORMANCE OF BRUSHLESS SYNCHRONOUS MACHINES USING ADVANCED CONTROL STRATEGY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Synchronous generators (SG) are key electromechanical converters widely used in power plants, where precise excitation control is crucial for maintaining voltage regulation and stability. The main limitation of the conventional brushless excitation (CBE) system is its inability to supply negative voltages to the field winding, which limits fast de-excitation during sudden load rejection and causes terminal-voltage overshoots. To address this issue, this paper proposes an advanced fuzzy brushless excitation (FABE) system integrating fuzzy logic control (FLC) with H∞ control to enhance the transient and steady-state performance of synchronous generators. The H∞ controller ensures robustness against disturbances, parameter uncertainties, and nonlinearities, while the FLC improves adaptability and dynamic response. The proposed hybrid approach enables faster de-excitation, reduced voltage peaks, and improved damping of oscillations. Simulation results demonstrate that the FABE system clearly outperforms the conventional excitation method in terms of voltage stability, dynamic response, and overall control performance under various operating conditions.
Keywords: Synchronous generator; Brushless excitation; Voltage regulation; H∞ control; Fuzzy logic controller